2012
DOI: 10.1071/hr12011
|View full text |Cite
|
Sign up to set email alerts
|

John Paul Wild 1923 - 2008

Abstract: Paul Wild stands tall among the founding fathers of modern radio astronomy. His early work became the foundation for all future research on solar radio bursts. He established the theory and identified the different types of radio bursts. He developed new types of instrument including the dynamic spectrograph and a radioheliograph to make two-dimensional movie images. His early interest in the radio spectrum of hydrogen led to analysis of the hyperfine structure of hydrogen emission and a publication that becam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…John Paul Wild (1923, Frater and Ekers [70], Frater et al [71]) was born in Sheffield, England. A gunnery and radar officer in the Royal Navy (1943)(1944)(1945)(1946)(1947), he was also involved in research trying to understand why early radar was sometimes jammed, later found to be due to radio interference from the active Sun 29 .…”
Section: -1950mentioning
confidence: 99%
See 1 more Smart Citation
“…John Paul Wild (1923, Frater and Ekers [70], Frater et al [71]) was born in Sheffield, England. A gunnery and radar officer in the Royal Navy (1943)(1944)(1945)(1946)(1947), he was also involved in research trying to understand why early radar was sometimes jammed, later found to be due to radio interference from the active Sun 29 .…”
Section: -1950mentioning
confidence: 99%
“…For example, the drawings from Australia by Walter Frederick Gale (1865-1945: Wood [292]) in 1892 suggested a land of oases. 70 The pursuit of water on Mars continues to this day [293].…”
Section: -1965mentioning
confidence: 99%
“…His career culminated with his appointment as Chairman of CSIRO in 1978. 11,12 During the meeting Wild insisted that 'the publication, if any, should be in the form of a journal that could be sold and referred to' and must have done so convincingly for a motion to rescind Proposal 9 was put but lost on a show of hands.…”
Section: The Beginnings Of Pasamentioning
confidence: 99%
“…Orchiston has completed his project on early French radio astronomy. Frater & Ekers (2012) have provided a biographical memoir of John Paul Wild. Ekers (2014) discusses the history of our understanding of non-thermal radio emission.…”
Section: Selected Publicationsmentioning
confidence: 99%